2018
DOI: 10.1007/s41686-018-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Supervision of Student Teachers as a Catalyst of Change for Educational Equity in Rural Areas

Abstract: This paper presents an in vivo naturalistic case study of an education college in a Midwestern state university that implemented Cisco TelePresence high-definition teleconference technology in supervising student teachers in rural schools. Guided by a clinical supervision triad model, this approach includes synchronous virtual observation and video-based non-synchronous reflective practice within a triad of university supervisor, student teacher, and cooperating teacher. Results demonstrate that important fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Another study using tablets as a digital tool showed that they can improve focus, strengthen motivation, increase feedback, increase opinion-sharing, improve coherence, improve structure, and improve preparation and reflection in the implementation of supervision, but its effect on the teacher teaching-learning process has not been studied [29]. Several studies on the use of virtual supervision for student guidance have shown effective results, but the effectiveness of communication techniques has not been studied [30][31][32]. The use of video conferencing in student supervision is felt to be more effective, but its effect on the learning process has not been proven [33].…”
Section: Ict-based Instructional Supervision and Teacher's Instructionmentioning
confidence: 99%
“…Another study using tablets as a digital tool showed that they can improve focus, strengthen motivation, increase feedback, increase opinion-sharing, improve coherence, improve structure, and improve preparation and reflection in the implementation of supervision, but its effect on the teacher teaching-learning process has not been studied [29]. Several studies on the use of virtual supervision for student guidance have shown effective results, but the effectiveness of communication techniques has not been studied [30][31][32]. The use of video conferencing in student supervision is felt to be more effective, but its effect on the learning process has not been proven [33].…”
Section: Ict-based Instructional Supervision and Teacher's Instructionmentioning
confidence: 99%
“…University supervisors play an essential role in helping to negotiate a space that connects the university to the school, all the while helping to facilitate the students' process of understanding, learning from, and making meaning of their daily work (Cuenca, 2013;Elfer, 2013;Thurlings et al, 2014;Graziano and Feher, 2016;Diacopoulos and Butler, 2020). Relationships are critical to gain the trust of the student-teacher and their school mentor teacher (Cuenca, 2013;Elfer, 2013;Liu et al, 2018). Investing in a relationship with the student is essential as part of the feedback process that supervisors employ will guide student teachers as they reflect on and learn about their work as teachers (Thurlings et al, 2014;Liu et al, 2018;Diacopoulos and Butler, 2020).…”
Section: Supervising Student Teachers and Online Supervisionmentioning
confidence: 99%
“…Relationships are critical to gain the trust of the student-teacher and their school mentor teacher (Cuenca, 2013;Elfer, 2013;Liu et al, 2018). Investing in a relationship with the student is essential as part of the feedback process that supervisors employ will guide student teachers as they reflect on and learn about their work as teachers (Thurlings et al, 2014;Liu et al, 2018;Diacopoulos and Butler, 2020). This process also involves helping teacher candidates learn to make sense of their teaching within a particular environment and recognize the different pulls and pressures that may impact the way they are performing in the classroom (Diacopoulos and Butler, 2020).…”
Section: Supervising Student Teachers and Online Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distance education can connect rural students with geographically distant experts [56], providing students a form of engagement by collaborating on questions or in-class problems with online instructors [5]. Virtual instruction can be as effective as face-to-face supervision and can address logistical issues stemming from the distance between university-based programs providing the STEM expertise and rural or urban schools [31]. However, this is not the case for all content areas, and students have often noted a lack of 'teacher immediacy' -a psychological closeness between teacher and students -in distance courses [10].…”
Section: Introductionmentioning
confidence: 99%